SARS-CoV-2 infection predicts larger infarct volume in patients with acute ischemic stroke - De Michele, Manuela; Lorenzano, Svetlana; Piscopo, Paola; Rivabene, Roberto; Crestini, Alessio; Chistolini, Antonio; Stefanini, Lucia; Pulcinelli, Fabio M.; Berto, Irene; Campagna, Roberta; Amisano, Paolo; Iacobucci, Marta; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background and purpose Acute ischemic stroke (AIS) is a fearful complication of Coronavirus Disease-2019 (COVID-19). Aims of this study were to compare clinical/radiological characteristics, endothelial and coagulation dysfunction between acute ischemic stroke (AIS) patients with and without COVID-19 and to investigate if and how the SARS-CoV-2 spike protein (SP) was implicated in triggering platelet activation. Methods We enrolled AIS patients with COVID-19 within 12 h from onset and compared them with an age- and sex-matched cohort of AIS controls without COVID-19. Neuroimaging studies were performed within 24 h. Blood samples were collected in a subset of 10 patients. Results Of 39 AIS patients, 22 had COVID-19 and 17 did not. Admission levels of Factor VIII and von Willebrand factor antigen were significantly higher in COVID-19 patients and positively correlated with the infarct volume. In multivariate linear regression analyses, COVID-19 was an independent predictor of infarct volume (B 20.318, Beta 0.576, 95%CI 6.077–34.559; p = 0.011). SP was found in serum of 2 of the 10 examined COVID-19 patients. Platelets from healthy donors showed a similar degree of procoagulant activation induced by COVID-19 and non-COVID-19 patients' sera. The anti-SP and anti-FcγRIIA blocking antibodies had no effect in modulating platelet activity in both groups. Conclusions SARS-CoV-2 infection seems to play a major role in endothelium activation and infarct volume extension during AIS.